Cell fusion and hybrids in Archaea: Prospects for genome shuffling and accelerated strain development for biotechnology - Naor, Adit (Landes Bioscience, 2013)
The ability to exchange DNA between cells is a molecular process that exists in different species in the domain Archaea. Such horizontal gene transfer events were shown to take place between distant species of archaea and to result in the transfer of large genomic regions. Here we describe recent progress in this field, discuss the potential use of natural gene exchange processes to perform genome shuffling and argue its possible biotechnological applications.